2019
DOI: 10.1186/s40478-019-0737-z
|View full text |Cite|
|
Sign up to set email alerts
|

Intrathecal delivery of recombinant AAV1 encoding hepatocyte growth factor improves motor functions and protects neuromuscular system in the nerve crush and SOD1-G93A transgenic mouse models

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neuromuscular disease resulting from motor neuron degeneration that causes muscle weakness, paralysis, and eventually respiratory failure. We investigated whether recombinant adeno-associated virus encoding human hepatocyte growth factor (rAAV-HGF) could generate beneficial effects in two mouse models with neuromuscular problems when intrathecally delivered to the subarachnoid space. We chose AAV serotype 1 (rAAV1) based on the expression levels and distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…In the spinal cord, we found that the neuroprotection was accompanied by the activation (phosphorylation) of ERK but not AKT. This result complies with a recent study showing that intrathecal delivery of recombinant AAV1 encoding HGF/SF protected spinal motor neurons in SOD1G93A mice through an increase in phosphorylated ERK but no other signaling molecules of the HGF/SF-MET pathway such as STAT3, cJUN and GSK3b [ 15 ]. This highlights the importance of ERK activation in the rescue of motor neurons induced by HGF/MET signaling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the spinal cord, we found that the neuroprotection was accompanied by the activation (phosphorylation) of ERK but not AKT. This result complies with a recent study showing that intrathecal delivery of recombinant AAV1 encoding HGF/SF protected spinal motor neurons in SOD1G93A mice through an increase in phosphorylated ERK but no other signaling molecules of the HGF/SF-MET pathway such as STAT3, cJUN and GSK3b [ 15 ]. This highlights the importance of ERK activation in the rescue of motor neurons induced by HGF/MET signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, certain residual anterior horn cells from post-mortem ALS patients overexpressed both HGF/SF and MET in comparison with those of normal subjects [ 13 ]. Most importantly, transgenic overexpression or intrathecal delivery of the growth factor markedly delayed the progression of the disease in SOD1G93A transgenic mice and rats [ 14 , 15 ]. Hence, early clinical trials involving intramuscular administration of plasmid HGF/SF DNA [ 16 ] or intrathecal delivery of HGF/SF protein [ 17 ] in ALS patients have displayed adequate safety profiles and are now progressing to efficacy studies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, HGF has been reported to be involved in the regeneration of peripheral nerves, and supplementation with this gene shows therapeutic effects in various peripheral neuropathy models [ 3 , 4 , 8 , 11 ]. HGF promoted the differentiation of repair-type Schwann cells by inducing AP-1 transcription factors and accelerated the outgrowth of injured axons through c-Jun protein [ 3 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, viral vector gene transfer has been tested pre-clinically and is more promising because it provides a more efficient transcription transfer than non-viral methods. Thus, gene therapy with viral vectors protects from neuronal death in animal models of ALS ( Lee et al, 2019 ) and cerebral ischemia ( Hayashi et al, 2001 ), promotes angiogenesis, and reduces apoptosis in SCI ( Kitamura et al, 2007 ). Moreover, HGF gene transfer with viral vectors reduces pain and inflammation in a neuropathic model ( Tsuchihara et al, 2008 ), promotes neurite extension, and increases synaptogenesis in a stroke model ( Shimamura et al, 2006 ).…”
Section: Therapeutical Potential Of Hgf and Hgf Mimetics In Neurological Disordersmentioning
confidence: 99%